Perubahan Struktur Tematik dalam Penerjemahan - Arif Fudiyartanto, Fuad (Adabiyyāt: Jurnal Bahasa dan Sastra, 2020)
Every translator seeks to find the equivalence of the source text in terms of meaning and style. In practice, translators often need to change the structure of their translations. This kind of techniques or methods of translation is often called shift. Shift can occur in different levels, which can include a clause, sentence, or paragraph level. By analyzing students’ translation using the perspective of Systemic Functional Linguistics by Halliday, this study finds several shifts in terms of theme-rheme classification and theme constituents. Shifts in theme-rheme classification can be categorized into: a) a change from rheme into theme, b) from theme into rheme, c) addition of textual theme, and d) deletion or omission of textual theme. In terms of theme constituents, shifts were found in four categories, namely a) shifts from a morpheme into a word, b) from a word into a phrase, c) from a phrase into a word, and d) from a clause into a word. These shifts have impacts on the meaning of the target texts as opposed to the source texts, at sentence or paragraph level.